2005
DOI: 10.1021/jp053425m
|View full text |Cite
|
Sign up to set email alerts
|

Real Structure of Formamide Entrapped by AOT Nonaqueous Reverse Micelles:  FT-IR and 1H NMR Studies

Abstract: Noninvasive techniques such as FT-IR and (1)H NMR spectroscopy have been employed to investigate the solubilization of formamide, FA, and its aqueous solution, FA-water, by sodium 1,4-bis(2-ethylhexyl)sulfosuccinate, AOT, in heptane or isooctane reverse micelles, respectively. Partially deuterated FA (FADH) was used in the FT-IR experiments and nu(OD), n(ND) were analyzed. Also, the nu(C=O) band of FA was investigated. For AOT, the changes of the SO(3)(-) group's symmetric, nu(s), and asymmetric, nu(a), bands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 98 publications
3
68
0
Order By: Relevance
“…FA is a "special" solvent since we demonstrated that FA encapsulated by AOT reverse micelles, interacts strongly with the Na + counterions and the sulfonate group of the surfactant through electrostatic interactions maintaining their hydrogen bond network present in the FA bulk. 42 Thus, it was expected, and actually observed, that the K b value in this system was similar to the one obtained at W S = 0 because the sulfonate group was involved in an electrostatic interaction in both reverse micelles. On the other hand, an interesting situation was observed when DMF and DMA were sequestrated by the reverse micelles since the K b values obtained were the highest.…”
supporting
confidence: 76%
“…FA is a "special" solvent since we demonstrated that FA encapsulated by AOT reverse micelles, interacts strongly with the Na + counterions and the sulfonate group of the surfactant through electrostatic interactions maintaining their hydrogen bond network present in the FA bulk. 42 Thus, it was expected, and actually observed, that the K b value in this system was similar to the one obtained at W S = 0 because the sulfonate group was involved in an electrostatic interaction in both reverse micelles. On the other hand, an interesting situation was observed when DMF and DMA were sequestrated by the reverse micelles since the K b values obtained were the highest.…”
supporting
confidence: 76%
“…In contrast, recent studies have shown that FA inside AOT reverse micelles conserves the bulklike intersolvent H-bond interactions. [25,29] Despite the fact that the AOT molecule has different regions in its moiety, where the different solvents can interact (see Herein, we report a study of the interactions between different nonaqueous polar solvents, namely, ethylene glycol (EG), propylene glycol (PG), glycerol (GY), dimethylformamide (DMF), and dimethylacetamide (DMA), and the polar heads of sodium 1,4-bis-2-ethylhexylsulfosuccinate (AOT) in nonaqueous AOT/nheptane reverse micelles. The goal of our study is to gain insights into the unique reverse-micelle microenvironment created upon encapsulation of these polar solvents.…”
Section: [Water]/a C H T U N G T R E N N U N G [Aot] = 10 (Aqueous) Wmentioning
confidence: 99%
“…To do this, we used different approaches: i) invasive techniques, such as absorption and emission spectroscopy of different molecular probes dissolved in different nonaqueous reverse micelles media, [16,17,19,28,29] and ii) noninvasive techniques, such as FTIR and 1 H NMR spectroscopy, [18,20,25] where the main effort was focused on the interpretation of the spectra of different polar solvents encapsulated inside reverse micelles to gain insights into their structure and the existence or not of a polar solvent pool. Thus, we have followed how the n OD or the n ND bands for EG, GY, PG, and FA change as the W S ratio increases.…”
Section: [Water]/a C H T U N G T R E N N U N G [Aot] = 10 (Aqueous) Wmentioning
confidence: 99%
See 1 more Smart Citation
“…16,37,38 ͑iii͒ Laia et al 39 performed light scattering experiments that would indicate that in formamide/AOT micelles the polar head groups ͑PHGs͒ are poorly solvated by formamide, leading to a strong association between the AOT polar heads and Na + counterions, resulting in an overall electrically neutral interfacial region. ͑iv͒ Finally, Correa et al 40 employed Fourier transform infrared and NMR techniques to explore the solubilization of formamide and its aqueous solutions by AOT in reverse micelles. Their results indicate that formamide interacts strongly with the Na + counterions, while preserving the HB network found in the bulk phase.…”
Section: Introductionmentioning
confidence: 99%